Barriers to knowledge sharing in Chinese healthcare referral services: an emergent theoretical model - Lihong Zhou; Miguel Baptista Nunes (Taylor & Francis Group, 2016)
Background: This paper reports on a research study that aims to identify and explain barriers to knowledge sharing (KS) in the provision of healthcare referral services in Chinese healthcare organisations. Design: An inductive case study approach was employed, in which 24 healthcare professionals and workers from four healthcare organisations in the province of Hubei, Central China, were interviewed using semi-structured scripts. Results: Through data analysis, 14 KS barriers emerged in four main themes: interpersonal trust barriers, communication barriers, management and leadership barriers, and inter-institutional barriers. A cause-consequence analysis of the identified barriers revealed that three of them are at the core of the majority of problems, namely, the absence of national and local policies for inter-hospital KS, lack of a specific hospital KS requirement, and lack of mutual acquaintance. Conclusions: To resolve KS problems, it is of great importance that healthcare governance agencies, both at the national and regional levels, take leadership in the process of KS implementation by establishing specific and strong policies for inter-institutional KS in the referral process. This paper raises important issues that exceed academic interests and are important to healthcare professionals, hospital managers, and Information communication technology (ICT) managers in hospitals, as well as healthcare politicians and policy makers.